Drosophila Atg9 regulates the actin cytoskeleton via interactions with profilin and Ena - Kiss, Viktória (Cell Death Differ, 2019)
Autophagy ensures the turnover of cytoplasm and requires the coordinated action of Atg proteins, some of which also have moonlighting functions in higher eukaryotes. Here we show that the transmembrane protein Atg9 is required for female fertility, and its loss leads to defects in actin cytoskeleton organization in the ovary and enhances filopodia formation in neurons in Drosophila. Atg9 localizes to the plasma membrane anchor points of actin cables and is also important for the integrity of the cortical actin network. Of note, such phenotypes are not seen in other Atg mutants, suggesting that these are independent of autophagy defects. Mechanistically, we identify the known actin regulators profilin and Ena/VASP as novel binding partners of Atg9 based on microscopy, biochemical, and genetic interactions. Accordingly, the localization of both profilin and Ena depends on Atg9. Taken together, our data identify a new and unexpected role for Atg9 in actin cytoskeleton regulation.